Evaluation of Controlled Release Patterns of Ornidazole using Bio-degradable Polymers and Determination of its Antibacterial Activity - Neurgaonkar, Mahesh; Kothiwale, Shaila Veerappa (Indian Journal of Pharmaceutical Education and Research, 2021)
Aim: Controlled release (CR) local drug delivery (LDD) devices are useful in periodontitis management since they facilitate prolonged maintenance of high antimicrobial concentrations in the periodontal pockets. The study aimed, to formulate and evaluate the in-vitro release pattern of Ornidazole (OZ) from three different biodegradable polymer films and to determine the antibacterial activity of released OZ on periodontal pathogens. Materials and Methods: Four samples of 3 LDD systems were formulated by incorporating OZ into 3 different biodegradable polymer films, viz. hydroxypropylmethyl cellulose (Group I), chitosan (Group II) and hydroxypropyl cellulose (Group III). The release of OZ from these formulations was studied spectrophotometrically. The antibacterial activity of the released OZ on periodontal pathogens was evaluated by determining the inhibition zone (IZ) area. Data was statistically analyzed using ANOVA. Results: OZ release and IZ of chitosan films were 6 days, HPMC 4 days and HPC films 3 days. In-vitro bio adhesion (5.50± 0.100 g), OZ concentration released and IZ area were greatest with chitosan films (p<0.05). HPMC films showed a significantly greater OZ release and IZ area compared to HPC films for the first 3 days (p<0.05). Conclusion: Chitosan incorporated with OZ may be considered as a suitable bioabsorbable CR LDD system as an adjunct to mechanical periodontal therapy.
Keywords: Chitosan; Local drug delivery; Hydroxypropylcellulose; Ornidazole; Periodontitis